2006
DOI: 10.1007/s11258-005-9092-1
|View full text |Cite
|
Sign up to set email alerts
|

Germination and seed water status of four grasses on moss-dominated biological soil crusts from arid lands

Abstract: Biological soil crusts dominated by drought-tolerant mosses are commonly found through arid and semiarid steppe communities of the northern Great Basin of North America. We conducted growth chamber experiments to investigate the effects of these crusts on the germination of four grasses: Festuca idahoensis, Festuca ovina, Elymus wawawaiensis and Bromus tectorum. For each of these species, we recorded germination time courses on bare soil and two types of biological soil crusts; one composed predominantly of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 45 publications
5
104
1
1
Order By: Relevance
“…This variation may be related to moss height, because if the moss grows high, surface seeds will not make contact with the soil, and moisture levels will be insufficient for germination. However in another study, Serpe et al (2006) observed that a biological soil crust dominated by short moss significantly inhibited germination of cheatgrass and three perennial grasses, while tall moss crust had little effect on germination, which is not in accordance with our results.…”
Section: The Barrier Effects Of Bscs On Seed Germinationcontrasting
confidence: 99%
“…This variation may be related to moss height, because if the moss grows high, surface seeds will not make contact with the soil, and moisture levels will be insufficient for germination. However in another study, Serpe et al (2006) observed that a biological soil crust dominated by short moss significantly inhibited germination of cheatgrass and three perennial grasses, while tall moss crust had little effect on germination, which is not in accordance with our results.…”
Section: The Barrier Effects Of Bscs On Seed Germinationcontrasting
confidence: 99%
“…De esta manera, la presencia de la CBS facilita o limita la germinación de semillas, según la especie de CBS y de planta (Serpe et al 2006;Escudero et al 2007;Langhans et al 2009). Finalmente, la CBS interacciona con otros microorganismos y microfauna del suelo, ya que les proporciona recursos y un hábitat potencial (Neher et al 2003;Bamforth 2004;Castillo-Monroy et al 2011b).…”
unclassified
“…We did not examine BSC coverage in this study but lichen, moss, and cyanobacterial crusts were present and our soil surface disturbance removed these BSC. Lichen crusts can reduce the abundance of B. tectorum by 85% possibly through reducing germination percentage or inhibiting root penetration of soil (Serpe et al 2006, Deines et al 2007). Disruption of BSC was likely more important than litter presence in hindering B. tectorum establishment in this study although the interaction of BSC removal and litter presence is largely unexplored.…”
Section: Discussionmentioning
confidence: 99%